3-D optical and electrical simulation for CMOS image sensors. - Mutoh, H.
The optical and electrical characteristics of CMOS image sensors, such as readout, saturation, reset, charge-voltage conversion, and crosstalk characteristics, are analyzed by a three-dimensional (3-D) device simulator SPECTRA and a 3-D optical simulator TOCCATA which were developed for the analysis of CCD image sensors. The model of readout operation for a buried photodiode with potential barrier and dip is discussed with consideration of thermal diffusion. The transient simulation is executed for readout and reset operation. A novel calculation method for photodiode saturation condition is proposed. The optical and electronic crosstalk is analyzed individually by ray-tracing and current calculation. It is found that the above methods successfully analyze the optical and electrical characteristics of CMOS image sensors.
Keywords: 3D device simulator; CMOS image sensors; SPECTRA; TOCCATA; Buried photodiode; Charge-voltage conversion; Crosstalk characteristics; Electrical characteristics; Photodiode saturation condition; Potential barrier; Ray-tracing.; Readout; Readout operation; Reset; Reset operation; Saturation; Thermal diffusion; Transient simulation